2010
DOI: 10.1016/j.jasms.2010.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric identification of oxidative modifications of tryptophan residues in proteins: Chemical artifact or post-translational modification?

Abstract: Oxidative modification of tryptophan to kynurenine (KYN) and N-formyl kynurenine (NFK) has been described in mitochondrial proteins associated with redox metabolism, and in human cataract lenses. To a large extent, however, previously reported identifications of these modifications were performed using peptide mass fingerprinting and/or tandem-MS data of proteins separated by gel electrophoresis. To date, it is uncertain whether NFK and KYN may represent sample handling artifacts or exclusively post-translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 23 publications
5
98
0
2
Order By: Relevance
“…For His-containing peptides R4-1 and P5-1 that exhibit multiple charge states, the dominant species were triply charged and quantification was based on only these species. Peak area analysis of the Trp-bearing peptide (P1-2) and its various oxidized forms (e.g., kynurenine, hydroxytryptophan, and dihydroxytryptophan; see also Perdivara et al, 2010) revealed that ;98% of P1-2 remained unoxidized.…”
Section: Lc-ms Analysis and Data Processingmentioning
confidence: 99%
“…For His-containing peptides R4-1 and P5-1 that exhibit multiple charge states, the dominant species were triply charged and quantification was based on only these species. Peak area analysis of the Trp-bearing peptide (P1-2) and its various oxidized forms (e.g., kynurenine, hydroxytryptophan, and dihydroxytryptophan; see also Perdivara et al, 2010) revealed that ;98% of P1-2 remained unoxidized.…”
Section: Lc-ms Analysis and Data Processingmentioning
confidence: 99%
“…Additionally, it may be difficult to ascertain whether the oxidation of highly reactive residues, such as methionine (181) or cysteine, represent artifacts upon sample handling, or true PTMs. Tomer and co-workers, have shown that tryptophan oxidation may occurs following to protein purification and isolation, particularly with the use of gel electrophoresis (182); and electrospray ionization has also been reported to induce oxidation of methionine, tryptophan or tyrosine residues (183).…”
Section: Detection and Enrichment Of Oxidative Post-translational Modmentioning
confidence: 99%
“…Further, it might be difficult to distinguish between biologically relevant PTMs and artifacts introduced during an analysis. For example, tryptophan oxidation is considered to be a natural irreversible PTM, but it has been recently found that kynurenine and N-formyl kynurenine tryptophan oxidation products can be introduced into a protein during SDS-PAGE separation [132].…”
Section: Troublesome Path Of Redox Proteomicsmentioning
confidence: 99%